Would you choose your preferred option? Comparing choice and recoded ranking experiments (AMERICAN JOURNAL OF AGRICULTURAL ECONOMICS, 2008)
Previous research has shown that results from a choice experiment are statistically different from those obtained from a ranking experiment that is recoded and treated as a choice experiment using only the first rank. By avoiding some of the shortcomings of previous comparisons, we obtain the opposite results using data from the valuation of a cork oak reforestation program in the south of Spain. Structural models and welfare estimations are statistically indistinguishable irrespective of the use of parametric or bootstrapping tests. Further, we employ follow-up questions and subsample analysis to test whether divergences appear when potential effects are isolated.